2015
DOI: 10.1103/physrevb.91.134113
|View full text |Cite
|
Sign up to set email alerts
|

Domain pinning near a single-grain boundary in tetragonal and rhombohedral lead zirconate titanate films

Abstract: The interaction of grain boundaries with ferroelectric domain walls strongly influences the extrinsic contribution to piezoelectric activity in Pb(Zr,Ti)O 3 (PZT), ubiquitous in modern transducers and actuators. However, the fundamental understanding of these phenomena has been limited by complex mechanisms originating from the interplay of atomic-level domain wall pinning, collective domain wall dynamics, and emergent mesoscopic behavior. This contribution utilizes engineered grain boundaries created by depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 57 publications
0
22
2
Order By: Relevance
“…Figure shows a demonstration of how these factors can be strongly dependent on composition. The reduction in piezoelectric activity near a grain boundary occurs over a length scale of ~800 ± 70 nm around the boundary itself in tetragonal PbZr 0.45 Ti 0.55 O 3 and only half that distance (450 ± 30 nm) for a morphotropic phase boundary composition, PbZr 0.52 Ti 0.48 O 3 . This difference is likely to be due to the fact that the more complex domain structure possible at the morphotropic phase boundary means that local stresses and fields can be accommodated in a smaller volume .…”
Section: Domain Grain Size and Thickness Scaling Effectsmentioning
confidence: 94%
See 1 more Smart Citation
“…Figure shows a demonstration of how these factors can be strongly dependent on composition. The reduction in piezoelectric activity near a grain boundary occurs over a length scale of ~800 ± 70 nm around the boundary itself in tetragonal PbZr 0.45 Ti 0.55 O 3 and only half that distance (450 ± 30 nm) for a morphotropic phase boundary composition, PbZr 0.52 Ti 0.48 O 3 . This difference is likely to be due to the fact that the more complex domain structure possible at the morphotropic phase boundary means that local stresses and fields can be accommodated in a smaller volume .…”
Section: Domain Grain Size and Thickness Scaling Effectsmentioning
confidence: 94%
“…Several groups have performed PFM characterization across grain boundaries in epitaxial films on bicrystal substrates. Bicrystal substrates enable properties near grain boundaries with preselected misorientation to be characterized . PFM data recorded across a 24° crystallographic tilt about [001] pc (where pc denotes pseudocubic indices) in BiFeO 3 demonstrated that grain boundaries can attract nearby domain walls and restrict the growth of the energetically preferred polarization direction .…”
Section: Domain Grain Size and Thickness Scaling Effectsmentioning
confidence: 97%
“…[14] However, the stress fields associated with each domain wall can result in complex interactions with local defects -be these point defects, dislocations, other domain walls or grain boundaries-, limiting or enhancing the mobility of the domain wall itself. [15,16] In fact, recent studies have illustrated the unexpectedly large role of clamping on the electromechanical response of PZT thin films, suggesting the presence of nontrivial, large length-scales for strain interactions present in such samples. [17] Similarly, evidence has also been provided of avalanche-like behavior of multiple domain walls due to cooperative interactions across these large length scales in disordered ferroelectric thin films.…”
Section: Introductionmentioning
confidence: 99%
“…According to Figure C,F, it is found from the vertical PFM images that the domain size of 0.25BNT‐0.75PT (C) is smaller than that of 0.35BNT‐0.65PT (F). This may be caused by the defects at the grain boundary, which pins the movement of the domain wall, further limiting the growth of the domains …”
Section: Resultsmentioning
confidence: 99%